2017
DOI: 10.21763/tjfmpc.296329
|View full text |Cite
|
Sign up to set email alerts
|

The Breastfeeding in Adolescent Mothers

Abstract: ÖZETDünya Sağlık Örgütü, adölesan dönemini 10-19 yaşları arasındaki dönem olarak tanımlamakta ve dünyada her altı kişiden birinin adölesan olduğunu bildirmektedir. Bu dönemde gerçekleşen fiziksel ve psikolojik değişiklikler, madde bağımlılığı, korunmasız cinsel ilişki ve istenmeyen gebelikler gibi bazı riskli davranışlara neden olabilmektedir. Hem gelişmiş, hem de gelişmekte olan ülkelerde adölesan gebelikler önemli bir sağlık sorunudur. Adölesan gebeliğin risk faktörleri, çok yönlü ve karmaşıktır. Abortus, er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Similarly, it has been reported that in South Africa, over 16 million girls aged 15–19, including one million under the age of 15, are giving birth, which is recognised as a severe public health issue. 6 , 7 , 8 Furthermore, the number of deliveries among South African girls aged 10–14 is said to have climbed by 48.7% from 2726 in 2017/2018 to 4053 in 2020/2021. 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been reported that in South Africa, over 16 million girls aged 15–19, including one million under the age of 15, are giving birth, which is recognised as a severe public health issue. 6 , 7 , 8 Furthermore, the number of deliveries among South African girls aged 10–14 is said to have climbed by 48.7% from 2726 in 2017/2018 to 4053 in 2020/2021. 3 …”
Section: Introductionmentioning
confidence: 99%
“…4 health issue. 6,7,8 Furthermore, the number of deliveries among South African girls aged 10-14 is said to have climbed by 48.7% from 2726 in 2017/2018 to 4053 in 2020/2021. 3 The United Nations (2015) Sustainable Development Goal 3 (targets 3.1 and 3.7) prioritises the need to reduce maternal and child mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that rates of initiation and duration of breastfeeding in adolescents are lower compared to adult mothers, and many of them breastfeed for less than 6 weeks (Işık & Cetişli, 2017; Nuampa et al., 2019). Also, it has been reported that between 15% and 18.7% of mothers under the age of 20 give breast milk exclusively for 6 months and only 5% until 1 year of age (Centers for Disease Control and Prevention, 2017; Martínez & Hermosilla, 2017), suggesting that between the first and second semesters of life a 45.6% reduction in the prevalence of breastfeeding among children of adolescents (Ferreira da was administered, Silva Junior et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors that affect the initiation, intention, and continuity of breastfeeding in adolescent mothers are insufficient social support from the mother and partner, socioeconomic disadvantages, negative attitudes and experiences, low level of knowledge and self‐efficacy, a perceived benefit of breastfeeding, cultural norms and prejudices, and nipple problems or discomfort including pain (Işık & Cetişli, 2017; Kanhadilok & McGrath, 2015; Leclair et al., 2015). In Colombia, some predictors of breastfeeding in young women have been reported, such as the newborn's hospitalization, the number of children, and pregnancy planning (Castillejo Padilla et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation